Combined antidiabetic benefits of exenatide and dapagliflozin in diabetic mice1. Issue 4 (9th December 2013) - Tatarkiewicz, K.; Polizzi, C.; Villescaz, C.; D'Souza, L. J.; Wang, Y.; Janssen, S.; Parkes, D. G.
<x xml:space="preserve">Abstract</x> The combined glucose‐lowering effect of exenatide and dapagliflozin has not yet been studied. We investigated this combination (single‐dose or 4‐week dosing) in diabetic ob/ob mice. Vehicle‐corrected basal glucose showed greater reduction 1 h following exenatide + dapagliflozin than with exenatide or dapagliflozin alone, and stayed significantly lower for all groups versus vehicle over 3 h. During an oral glucose tolerance test, glucose excursion (30 min post‐dose) was significantly lower for exenatide + dapagliflozin versus exenatide or dapagliflozin, or vehicle. Exenatide + dapagliflozin and exenatide, but not dapagliflozin alone, reduced glucose excretion over 24 h versus vehicle. After dosing for 4 weeks, exenatide, dapagliflozin and exenatide + dapagliflozin similarly decreased haemoglobin A1c (HbA1c). Body weight was reduced only with exenatide or exenatide + dapagliflozin. The glomerular filtration rate was similar with exenatide, dapagliflozin and vehicle, and increased with exenatide + dapagliflozin. Optimized combinatorial dosing of these antidiabetic agents may provide additive glucose lowering in type 2 diabetes mellitus.